Analysis of energy consumption for Algerian building in extreme North-African climates - Kadraoui, Hicham; Chikhaoui, Abdelhak; Bekkouche, Sidi Mohammed El amine (International Journal of Sustainable Energy Planning and Management, 2019)
The objective of this study is to diagnose and quantify energy consumptions of a real residential building with local materials. Three sites belong to different radiative regimes: Algiers on the southern Mediterranean shore, Tlemcen on the west and Ghardaïa in the Sahara of Algeria. The followed method is based on an approach for assessing heating and cooling energy needs, solar gains, internal lighting loads, occupants and equipment are not considered. Annual heating and cooling requirements are calculated, according to climate data from 2014. We are also interested in a technical and economic study to have a monthly and annual estimation of heating and cooling needs in kilowatt hours and Algerian money per m3 (DA / m3). The results show that this residential building is not affordable to live in. Facade walls, roof and ground are the major sources of heat losses in buildings (more than 70% of the total losses). The evaluation is devoted to adapt the construction to the region's climate. To improve the building's energy performance, it is necessary to integrate passive and active architectural concepts.